"Peru is a silent country": A Lost Opportunity for Cultural Exchange in "Тhe Royal Hunt of the Sun" - Tučev, Nataša R. (Collection of Papers of the Faculty of Philosophy in Priština, 2023)
In his renowned Discourse on Colonialism (1950), Aime Cesaire points out that the kind of contact which was typically established when the European colonizers encountered other civilizations was not wholesome or mutually beneficial, as the Europeans rarely made any genuine effort to acknowledge the values and achievements of other cultures; instead, their focus was primarily on exploitation and material gain. Such dynamic is also evident in Peter Shaffer’s play The Royal Hunt of the Sun (1964), where most of the members of the sixteenth-century Spanish expedition to Peru treat the Inca culture with hostility and disdain, or even regard some of its aspects as a threat which needs to be eliminated. The exceptions to this attitude may be found at the individual level, where some attempts at recognizing the cultural values of the Other are made by the protagonist, Pizarro, and the narrator, Martin. The paper examines these attempts, but aims to demonstrate that, in the final analysis, they also fail, so that Shaffer’s play as a whole conveys a message that imperialist ambitions inevitably undermine any opportunity for a beneficial cross-cultural encounter. In addition to Cesaire, other authors in the field of postcolonial and ideological criticism, such as Chinua Achebe, Salman Rushdie, Edward Said, and Roland Barthes will also be referred to.